Applying Software-Defined Networks technology to data aggregation in Wireless Sensor Network to improve its performance - علي, مريم; جمال خليفة , (Latakia University Journal -Engineering Sciences Series, 2023)
In this article, we present a proposed methodology in order to improve the performance of aggregation operations in Wireless Sensor Networks, by implementing Software-Defined Networking technology through the (SD-WISE) platform, In order to achieve the separation between the control plane and the data plane, we specifying the conditions for selecting the aggregated nodes in the controller by adjusting the weights of the (Dijekstra) algorithm, and based on the paths chosen by the algorithm, The aggregated nodes were determined based on the parameter of the paths that include the node, in addition to that the SDN-WISE platform depends on the state (Stateful) and implements what It is called the Finite State Machine, which helped us get rid of the limitations of traditional methods in applying software-defined networking technology in wireless sensor networks, as it supports reading the payload of the packet, not just the header, in addition to the ability to deal with a packet depending on another packet, and flexibility in Modify the routing tables in order to achieve the appropriate rules for the proposed aggregation algorithm.